Searching for the value of accountable care organizations in cancer care. Issue 22 (12th November 2018) - Modi, Parth K.; Hollenbeck, Brent K.; Borza, Tudor
Abstract : The impact of value‐based health care payment programs on cancer care is not well understood. As accountable care organizations and other alternative payment models continue to grow, understanding their intended and unintended effects will be essential to refining these policies.